HUBUNGAN PIJAT BAYI DENGAN PERKEMBANGAN MOTORIK KASAR PADA BAYI USIA 3-6 BULAN DI NARESWARA MOM AND BABY CARE KUDUS 2022: The relationship between baby massage and gross motor development in infants aged 3-6 months at Nareswara Mom and Baby Care Kudus 2022 - Khoiroh, Nidaul; Muawanah, Siti; Purnomo, M. Zuhal (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
Baby massage can stimulate the development of baby's gross motor skills, which is part of motor activity that involves large or gross muscle skills. The ability to use large muscles for babies is a basic movement ability. The purpose of this study is to analyze the relationship between infant massage and gross motor development in infants aged 3-6 months at Nareswara Mom and Baby Care Kudus. This study uses a quantitative method with a cross-sectional approach. The research sample consisted of 50 infants aged 3-6 months at Nareswara Mom and Baby Care, Kudus, with the sampling technique using total sampling. Analysis of research data using univariate and bivariate analysis using chi square. The results of the univariate analysis showed that there were 33 babies (66%) aged 3-6 months who were in the routine category, while there were 17 babies (34%) who were in the non-routine category. Furthermore, gross motor development was normal in 24 infants (48%), gross motor development in question was in 17 infants (34%), and gross motor development was deviant in 9 infants (18%). The results of the bivariate analysis showed that 22 respondents (44%) had normal gross motor development for infants aged 3-6 months who had regular massages, 9 respondents had doubts (18%), and 2 respondents had deviations (4%). Furthermore, infants aged 3-6 months in the non-routine category with normal gross motor development were 2 respondents (4%), doubtful 8 respondents (16%), and deviant 7 respondents (14%). Then the results of the chi square test show the sig. Asyim (P-Value) of 0.000 is less than 0.05 (0.000 <0.05). Statistically, there is a relationship between infant massage and gross motor development for infants aged 3-6 months at Nareswara Mom and Baby Care, Kudus. Thus it is hoped that mothers who have babies routinely provide baby massage stimulation in order to improve the baby's gross motor development.